FROM AWARENESS TO ACTION: A SYSTEMATIC LITERATURE REVIEW OF TEACHING MATERIALS BASED ON EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) - Rizky Agassy Sihombing; Muslim Muslim; Taufik Rahman (Jurnal Pembelajaran Sains, 2024)
Education for Sustainable Development (ESD) is crucial for equipping learners with the skills and knowledge needed to address global sustainability challenges. This research employs a Systematic Literature Review (SLR) methodology to evaluate the effectiveness of ESD-based teaching materials across various educational levels. Utilizing databases such as Google Scholar, SINTA, and Scopus, the study reviews articles focusing on the integration of ESD in formal education. The findings indicate that ESD-based materials significantly enhance students' critical thinking skills, sustainability awareness, and problem-solving abilities. These materials are deemed valid and practical by both experts and students, and they effectively facilitate the understanding and application of scientific principles to real-world problems. The study underscores the importance of incorporating ESD into educational curricula to foster a generation equipped to tackle environmental and societal challenges. Additionally, the use of digital tools and e-platforms proves effective in promoting sustainability education. Overall, the integration of ESD in education is vital for promoting sustainable development and improving the quality of education across primary, secondary, and higher education levels, particularly in disaster-prone regions like Indonesia.